To the question of the formation of reading students literacy as future subject teachers (Eurasian Journal of Philology Science and Education, 2020)
This article is devoted to the actual question of the state of reading literacy in modern society. In this regard, higher education is faced with an important task – the formation of reading literacy of future subject teachers who study Russian as non – native, which is reflected in the material under study.The article analyzes the concepts and semantic content of such terms as «reader literacy», «reader competence» and «reading culture».The topic of the formation of reading literacy of non-philology students by the authors of this article is proposed based on work with educational scientific text. After all, the text, representing an important communicative act of written verbal communication, contributes to the development and improvement of various reading skills and abilities, the capacity to understand and comprehend written texts, to use their content to achieve their own goals, to develop knowledge and opportunities oriented not only to vocational training but also on a harmoniously developed personality.The material of the textbooks on the Russian language intended for future subject teachers, gives examples of working with educational scientific text on the development and improvement of skills in the formation of reading literacy, not only using traditional forms of work, but also tasks aimed at innovative learning technologies in the field of vocational-oriented learning. In conclusion, referred to that the development of reading literacy skills and abilities are aimed at both improving professional competencies and developing general cultural competencies of the younger generation.